Version‐based and risk‐enabled testing, monitoring, and visualization of microservice systems. Issue 10 (18th January 2022) - Ma, Shang‐Pin; Liu, I‐Hsiu; Chen, Chun‐Yu; Wang, Yu‐Te
Abstract: Despite the growing importance of the microservice architecture (MSA), interactions among the various elements (e.g., services, endpoints, and versions) remain difficult to manage. This research devised a system, called version‐based microservice analysis, monitoring, and visualization (VMAMV), including multiple proposed methods to facilitate the testing, monitoring, and visualization of microservice systems by considering service versions and risks. VMAMV can generate version‐based service dependency graphs, provide graph search services, perform consumer‐driven contract testing, and conduct a risk analysis. Besides, VMAMV can also notify users of existing anomalies and potential risks to facilitate the development and operation of microservice systems. Experiments were conducted to demonstrate the efficacy of the VMAMV system in the detection of service anomalies, old patch versions, low‐usage service versions, the presentation of contract test results and service error chains, and the validity of risk analysis. Abstract : This research devised a system, called version‐based microservice analysis, monitoring, and visualization (VMAMV), including multiple proposed methods to facilitate the testing, monitoring, and visualization of microservice systems by considering service versions and risks. VMAMV can generate version‐based service dependency graphs, provide graph search services, perform consumer‐driven contract testing, and conduct a risk analysis. VMAMV can also notify users of existing anomalies and potential risks to facilitate the development and operation of microservice systems.